Investigation of the Relationship Between Computational Thinking and Design Thinking Skills of Science Teacher Candidates - Hakan Türkmen; Şahsenem Öz (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: Today's problems, which affect society and the environment, require individuals to have comprehensive skills. In this regard, it is essential to possess Computational Thinking (CT) and Design Thinking (DT) because it encompasses many dimensions and facilitates learning. Since DT processes are production-oriented, they can concretize computational processes that seem abstract to students. Therefore, using DT and CT together can improve both skills' development. However, it is seen that there needs to be a gap in investigating the relationship between CT and the DT skills of science teacher candidates. Therefore, the current research investigated the relationship between CT and DT skills among 94 science teacher candidates in the first and fourth years of their education and whether their skills differed based on grade level. Method: For this objective, a relational research model from quantitative research methodologies was utilized to understand whether variables interacted and gain valuable insights. Results: The results showed a positive relationship between science teacher candidates' CT and DT skills. Moreover, their skills differed according to grade level. Novelty: In this respect, this research contributes to the literature by stating that it could be beneficial to incorporate CT and DT skills in courses designed to acquire these two skills.